Generalised peripheral nerve dysfunction in acromegaly: a study by conventional and novel neurophysiological techniques. Issue 7 (July 1987) - Jamal, G A; Kerr, D J; McLellan, A R; Weir, A I; Davies, D L
Abstract : Twenty four patients with clinical, radiological and biochemical evidence of acromegaly were investigated by a number of independent neurophysiological tests. Two-thirds of the patients showed evidence of generalised peripheral nerve dysfunction. A significant correlation was found between total exchangeable body sodium, an indicator of disease activity, and the severity of the neuropathy. The generalised peripheral nerve abnormality was found to occur independently of the associated carbohydrate intolerance human growth hormone levels and other endocrinological dysfunction in this disorder.